Minimization of carryover for high‐throughput liquid chromatography with tandem mass spectrometry analysis of 14 mycotoxins in corn grits. Issue 13 (July 2014) - Tamura, Masayoshi; Matsumoto, Keiko; Watanabe, Jun; Iida, Junko; Nagatomi, Yasushi; Mochizuki, Naoki
<x xml:space="preserve">Abstract</x> (J. Sep. Sci. 2014, 37 (13), 1552–1560) DOI: 10.1002/jssc.201400099 Corn is a major crop, but there is risk of contamination of mycotoxins. Because fumonisin, one of the mycotoxins, adsorb on the metal in the analyzer, there is a problem in analytical accuracy. Therefore, to suppress the adsorption of fumonisin, a method for the simultaneous analysis of 14 mycotoxins was developed. It could be shown that this newly developed method is highly sensitive and with high accuracy. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>